Morphological characterization within and between populations of two Nigerian chicken ecotypes - Gambo, D.; Sabuwa, M. A.; Guluwa, L. Y.; Maichiki, W. P.; Baba, M. K.; Agbu, C. S. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The study was undertaken to investigate morphological variations within and between selected populations of the Nigerian Tiv and Fulani chicken ecotypes. The experiment was carried out in ten randomly selected localities across three states comprising Benue, Nasarawa and Plateau. The locations (1-5) for the Tiv ecotype were Uikpan, Daudu, Kadarko, Yelwata and Cohor while that of Fulani ecotype were Lafia, Akurba, Adogi, Asakio and Namu. One hundred (100) birds per location and a total of one thousand birds (1000) birds (500 each for Tiv and Fulani ecotypes) were used for the experiment. Data were collected on morphological characteristics such as plumage colour, shank colour, beak colour, comb colour, comb type, eye colour, skin colour, eye colour and wattle colour by physical visualization. Data collected were analyzed using simple statistical tools such as percentages. The results indicate that plumage and shank colour were predominantly brown and yellow respectively in both ecotypes. Black beak was predominant in the Tiv ecotype while brown beak dominated in the Fulani ecotype. Single comb-type overwhelmingly dominated in both ecotypes across locations. The comb colour was 100 percent red in both ecotypes across locations. Yellow eye colour dominated in all locations and in both ecotypes. Similarly, red wattle colour followed by dark red dominated in both ecotypes across locations. From the findings of this research, it was concluded that the Tiv and Fulani local chicken ecotypes should each be subjected to selection for uniformity in morphological traits as a necessary step to breed definition.